Optimizing Batik MSMEs through the implementation of green economy and sustainable digitalization - Ufi Rumefi; Harfiahani Indah Rakhma Ningtyas; Wildan Maualim (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
The Nona Alif Muclisin MSME in Pasuruan Regency faces challenges in the batik industry, particularly environmental pollution caused by synthetic dyes and limitations in global marketing. This community service program aims to address these challenges by applying green economy principles and digital marketing strategies. Through training sessions, the MSME was taught environmentally friendly waste management practices and the use of natural dyes to reduce pollution. Additionally, digital marketing training was provided to expand market reach and enhance the global visibility of batik products. The program also included tree planting initiatives as a source of natural dyes and an effort to mitigate environmental impacts. The results showed a significant reduction in environmental pollution through the adoption of natural dyes and improved waste management. The implementation of digital marketing strategies successfully expanded the MSME’s market and increased product sales. In conclusion, this program effectively addressed environmental and marketing challenges in batik MSMEs. However, continuous follow-up is needed to ensure the sustainability of positive outcomes and to support the future development of MSMEs.